(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Various non-governmental organizations and individuals have accused the Sri Lankan government of committing state terrorism. These allegations characterize much of the Sri Lankan government’s handling of insurgent groups dating from 1956, including the civil war againstTamil militant groups and the state response to the Janatha Vimukthi Peramuna insurrections, as state terrorism.